Method of Selecting Retention Tools in Managing Voluntary Employee Turnover - Marcin NOWAK; Marta PAWŁOWSKA-NOWAK (Communications of International Proceedings, 2024)
Voluntary employee turnover poses significant challenges in human resource management, particularly in retaining key talent within organizations. The aim of this article is to present a new method for selecting retention tools to manage voluntary employee turnover effectively. Addressing a gap in the literature on targeted retention strategies, this study introduces an innovative approach for identifying retention tools tailored to mitigate turnover. Employing the DEMATEL method for multi-criteria relational analysis, the article demonstrates a structured process that aligns retention tools with talent management objectives. The findings contribute to theory by advancing practices in talent management and provide managers with practical, data-driven tools to improve employee retention.
Keywords: voluntary employee turnover; talent management; employee retention; DEMATEL method